Leadership ambidexterity: Key to stimulating team learning through team-oriented HRM? An explorative study among teacher teams in VET colleges. (September 2019) - Bouwmans, Machiel; Runhaar, Piety; Wesselink, Renate; Mulder, Martin
In vocational education and training (VET) colleges worldwide, teacher teams work on innovations to improve their educational quality. To foster this process, teams benefit from team-oriented human resource management (HRM) aimed at stimulating teachers' team learning. This qualitative study explores in-depth how team leaders enact team-oriented human resource practices and how this affects teachers' perceptions of these practices and their engagement in team learning. Interviews with four team leaders and group interviews with 11 teachers from these four teams were conducted in one VET college in the Netherlands. The results showed that team leaders were both controlling and stimulating in their enactment. To foster team learning, it appears not just necessary that team leaders' enactment and teachers' perceptions of this enactment should be aligned, but that team leaders' enactment also should be geared towards the team's needs. This study therefore shows team leaders' crucial role in the effective implementation of team-oriented HRM in VET colleges.